Cortisol-Metabolizing Enzymes in Polycystic Ovary Syndrome. (January 2016) - Blumenfeld, Zeev; Kaidar, Gabi; Zuckerman-Levin, Nehama; Dumin, Elena; Knopf, Carlos; Hochberg, Ze'ev
Objective: The aim of this study was to assess the activity of cortisol-metabolizing enzymes in women with polycystic ovary syndrome (PCOS), using a fully quantitative gas chromatography/mass spectrometry (GCMS) method. Design: We investigated the glucocorticoid degradation pathways that include llβ-hydroxysteroid dehydrogenase (llβ-HSD) type 1, 5α-reductase (5α-R) and 5β-reductase (5β-R), 3α-hydroxysteroid dehydrogenase, and 20α- and 20β-hydroxysteroid dehydrogenase (20α-HSD and 20β-HSD, respectively) in young nonobese women with PCOS, using a fully quantitative GCMS method. Setting: This study was conducted in a tertiary referral hospital in Israel. Patients: This study group consisted of 13 young women, aged 20.1 ±2.8 years (mean ± SD), with the body mass index (BMI) of 22.6 ± 3.7 kg/m 2, diagnosed with PCOS according to the Rotterdam criteria. The control group consisted of 14 healthy young women matched for weight, height, and BMI. Interventions: Urine samples were analyzed using GCMS. We measured urinary steroid metabolites that represent the products and substrates of the study enzymes and calculated the product/substrate ratios to represent enzyme activity. Main Outcome Measures: The calculation of enzymatic activity, based on glucocorticoid degradation metabolites, was done by GCMS in PCOS vs. controls. Results: All glucocorticoid degradation metabolites were higher in the PCOS group than in controls. Of the adrenal enzymes, the activities of 21-hydroxylase and 17α-hydroxylase were reduced, whereas the activity of 17, 20-lyase was enhanced in PCOS. Of the degradation enzymes, the activity of 11β-HSD type 1 was reduced in women with PCOS only when calculated from cortoles and cortolones ratios. The activities of 5α-R/5β-R were increased only when calculating the 11-hydroxy metabolites of androgens. The activity of 20α-HSD was elevated in the patients with PCOS and its relation with the substrate levels was lost. Conclusions: We confirm PCOS association with low 21-hydroxylase activity. PCOS is associated with dysregulation in glucocorticoid degradation. The activity of 5α-R is enhanced only through the backdoor pathway. Marked increase in the activity of 20α-HSD suggests a hitherto unknown derangement in PCOS.